Factors associated with urinary incontinence in a community sample of young nulligravid women. Issue 5 (23rd April 2020) - Kowalik, Casey G.; Daily, Adam; Goodridge, Sophia D.; Hartigan, Siobhan M.; Kaufman, Melissa R.; Fowke, Jay H.; Dmochowski, Roger R.; Reynolds, William S.
Abstract: Aims: The aim of this study is to identify factors associated with urinary incontinence (UI) in a community sample of young nulligravid women. Methods: This was a secondary analysis from a cross‐sectional survey‐based study of cisgender women aged 18 to 25 years recruited through a national registry of research volunteers. Participants completed validated questionnaires assessing toileting behaviors, lower urinary tract symptoms (LUTS), and bowel symptoms. Women were excluded from analysis if currently pregnant, any prior pregnancy, cystectomy, or any neurologic disease including spinal cord injury, stroke, or multiple sclerosis. Analyses determined the prevalence of symptoms and evaluated candidate risk factors for UI. Results: Final analyses included 964 women (mean age, 22.6 ± 2.0). Monthly UI was identified in 295 (30.6%) subjects, with mixed UI being the most common (56.9%; n = 168). Seventy‐two women (7.4%) reported fecal incontinence (FI) and 24 (3.5%) women reported both UI and FI. After multivariable regression modeling, UI was associated with an intermittent urine stream and the delayed voiding toileting behavior subscale. Conclusions: UI in this cohort of young nulliparous women was highly prevalent and warrants further study as to the cause. Therapeutic guidelines to prevent UI and LUTS may need to be adjusted by targeting populations earlier than traditionally considered.